EFFECTIVENESS OF STUDENTS' DIRECTIVE SPEECH ACTS COMMUNICATION PATTERNS AT SMKN 2 PALU - Indriani Rais, Fajrin; Yunidar; Ulfah; Ida Nur'aeni; Mohammad Tahir (JURNAL KONFIKS, 2026)
This study aims to describe the patterns and effectiveness of directive speech acts used by students of the Visual Communication Design (DKV) Department under the Merdeka Curriculum at SMKN 2 Palu, particularly in the context of promoting their design products. The study combines qualitative analysis of directive forms (inviting, requesting, suggesting, commanding) with quantitative measurement of communication effectiveness using a Likert scale. The findings reveal that students predominantly use inviting and suggesting speech acts, while requesting and commanding occur less frequently. Based on Berlo’s SMCR model, the suggesting directive emerges as the most effective form due to its combination of politeness, clarity of intention, and persuasive power, whereas requesting shows the lowest effectiveness. Social factors such as gender, age, local dialect use, and learning environment influence students’ communication patterns. The Chi-Square test indicates a significant relationship between types of directive speech acts and their levels of effectiveness (p < 0.05). These findings highlight the need to strengthen students’ professional communication competence within the DKV learning framework, particularly in the context of the Merdeka Curriculum and Teaching Factory, to enable students to promote their design works more persuasively and in alignment with industry standards